Manajemen barang milik daerah berbasis kemitraan dalam meningkatkan sumber pendapatan daerah - Yasin Yasin; Fadillah Putra; Oscar Radyan Danar (Universitas Merdeka Malang, 2021)
The purpose of this study is to examine partnership-based regional property management in increasing local revenue sources for the Bima Regency government, and to analyze the factors that support and hinder partnership-based regional property management in realizing an increase in regional original income with the concept of Collaborative Governance. This type of research is a qualitative research that was chosen to describe the implementation of regional asset management in the form of leased land carried out by the DPPKAD Bima Regency, West Nusa Tenggara (NTB) using interactive model data analysis from Miles, Huberman and Saldana. The results showed that in general, partnership-based regional property management in increasing local revenue sources at the DPPKAD Bima Regency did not go well but showed an increase in regional original income, with supporting factors, among others; good quality/level of human resources education, a supportive work environment, and adequate infrastructure. While the inhibiting factors are regulations that do not reach the partnership process and the low level of program socialization.